Crosstalk between Cdk5 and GSK3β: Implications for Alzheimer's Disease - Engmann, Olivia; Giese, Karl P. (Frontiers in Molecular Neuroscience, 2009)
GSK3β and Cdk5 are the two kinases in the center of research on Alzheimer's disease (AD), involved in the pathological symptoms of AD, Aβ plaque formation, tau hyperphosphorylation and neurodegeneration. So far, both kinases have mostly been examined in isolation, leading to a schism of the research field into defenders of the GSK3β-versus the Cdk5 hypotheses of AD. However, in this debate the fact that activities of GSK3β and Cdk5 can influence each other deserves more attention. Recent evidence from p25 transgenic mice suggests that there is a dynamic crosstalk: during aging or prolonged overactivation of Cdk5, GSK3β activity may alter in favor of AD pathogenesis. In this review we summarize the connections between GSK3β and Cdk5 and discuss implications for AD hypotheses.